A qualitative study of health experiences of Ethiopian asylum seekers in Norway - Yvette Louise Schein; Brita Askeland Winje; Sonja Lynn Myhre; Ingunn Nordstoga; Melanie Lindsay Straiton (BMC, 2019)
Abstract Background Norway, like other European countries, has a growing refugee population. Upon arrival to Norway, refugees and asylum seekers need to learn about Norwegian society and social services such as healthcare. Despite various programs and assistance, they face numerous challenges using the healthcare system. Understanding the healthcare experiences of Ethiopian refugees and asylum seekers may improve how services such as informational sessions and delivery of medical care are provided. This qualitative study seeks to describe the health-related experiences of Ethiopians who have sought asylum in Norway and shed light on potential barriers to care. Methods Individual interviews were conducted with ten Ethiopian refugees and asylum seekers in Norway. Thematic analysis was used to understand the broader context of refugee resettlement and how this experience influences participants' health experiences and health seeking behaviors. Results We identified three main themes that played a role in participants' health and healthcare experiences. Participants described how 'living in limbo' during their application for residency took a mental toll, the difficulties they had 'using the healthcare system', and the role 'interpersonal factors' had on their experiences. While applying for asylum, participants felt consumed by the process and were affected by the lack of structure in their lives, the conditions in the reception center, and perceived inadequate healthcare. Participants perceived a change in access to services before and after they had been granted residency. Participants learned about the healthcare system both through official information sessions and social networks. Doctor-patient communication and interpersonal factors such as a sense of feeling valued, language, and discrimination had a large impact on perceived quality of care. Conclusions Ethiopian refugees and asylum seekers face numerous challenges accessing, using, and interacting with Norway's healthcare system. Contextualizing these challenges within the asylum seeking process may help policy makers better understand, and therefore address, these challenges. Interventions offered at reception centers and in health worker trainings may improve healthcare experiences for this and similar populations.